A pentaplex real-time PCR assay for rapid identification of major beta-lactamase genes KPC, NDM, CTX, CMY, and OXA-48 directly from bacteria in blood. Issue 12 (8th December 2021) - Hoj, Taalin R.; McNeely, Bradley; Webber, Kylie; Welling, Evelyn; Pitt, William G.; Ford, Larry C.; Robison, Richard A.
Abstract : Introduction. Antibiotic resistance, particularly in cases of sepsis, has emerged as a growing global public health concern and economic burden. Current methods of blood culture and antimicrobial susceptibility testing of agents involved in sepsis can take as long as 3–5 days. It is vital to rapidly identify which antimicrobials can be used to effectively treat sepsis cases on an individual basis. Here, we present a pentaplex, real-time PCR-based assay that can quickly identify the most common beta-lactamase genes ( Klebsiella pneumoniae carbapenemase (KPC); New Delhi metallo-beta-lactamase (NDM); cefotaximase-Munich (CTX-M); cephamycin AmpC beta-lactamases (CMY); and Oxacillinase-48 (OXA-48)) from pathogens derived directly from the blood of patients presenting with bacterial septicemia. Aim. To develop an assay which can rapidly identify the most common beta-lactamase genes in Carbapenem-resistant Enterobacteriaceae bacteria (CREs) from the United States. Hypothesis/Gap Statement. Septicemia caused by carbapenem-resistant bacteria has a death rate of 40–60 %. Rapid diagnosis of antibiotic susceptibility directly from bacteria in blood by identification of beta-lactamase genes will greatly improve survival rates. In this work, we develop an assay capable of concurrently identifying the five most common beta-lactamase and carbapenemase genes. Methodology. Primers and probes were created which can identify all subtypes of Klebsiella pneumoniae carbapenemase (KPC); New Delhi metallo-beta-lactamase (NDM); cefotaximase-Munich (CTX); cephamycin AmpC beta-lactamase (CMY); and oxacillinase-48 (OXA-48). The assay was validated using 13 isolates containing various PCR targets from the Centre for Disease Control Antimicrobial Resistance Isolate Bank Enterobacterales Carbapenemase Diversity Panel. Blood obtained from volunteers was spiked with CREs and bacteria were separated, lysed, and subjected to analysis via the pentaplex assay. Results. This pentaplex assay successfully identified beta-lactamase genes derived from bacteria separated from blood at concentrations of 4–8 c.f.u. ml −1 . Conclusion. This assay will improve patient outcomes by supplying physicians with critical drug resistance information within 2 h of septicemia onset, allowing them to prescribe effective antimicrobials corresponding to the resistance gene(s) present in the pathogen. In addition, information supplied by this assay will lessen the inappropriate use of broad-spectrum antimicrobials and prevent the evolution of further antibiotic resistance.